Financial turmoil and earnings mobility - Naguib, Costanza (Universität Bern, Faculty of Business, Economics and Social Sciences, Department of Economics, 2022)
We analyze how earnings dynamics changed in the US after the financial crisis of 2007- 2009. Differently from most models for earnings mobility, we allow persistence patters to depend semi-nonparametrically on both the past individual position in the distribution and on a set of individual-level covariates. Allowing for more flexibility in the model yields a better fit to the data and permits us to uncover changes in earnings mobility patterns that would otherwise remain hidden. Indeed, at the aggregate level, we find no evidence of changes in individual positional persistence in any part of the earnings distribution after the crisis, both with the parametric and with the semi-nonparametric model. However, the semi-nonparametric copula allows us to uncover an increase in earnings mobility for 45-year-old workers with college degree after the crisis.
10419/266513
Keywords: Graue Literatur; earnings dynamics; positional persistence; financial crisis; functional copula model; semi-nonparametric estimation